Perancangan Video Iklan Sebagai Media Promosi Pada Jasa Bordir Komputer Berbasis Animasi 3D - Amartya, Zilla; Khairani, Sumi; Sarudin, Sarudin (Ali Institute of Research and Publication, 2024)
The embroidery services business in Indonesia, starting from mid-2009, has begun to show its prospects. Until early 2016, the embroidery service business was growing rapidly since the advent of computer embroidery. Currently, many computer embroidery service owners are competing for the continuity of the service. Competition cannot be separated from advertising media aimed at promoting products and services. The problem in this research is how to promote computer embroidery services in increasing business productivity, how to introduce the public to computer embroidery services and how to design promotional advertising videos based on 3D animation. The computer embroidery business currently only relies on catalogs, where catalogs are only able to display information in the form of images in 2 dimensions to carry out promotions, so it needs to be developed further to create an attractive computer embroidery business model so that consumers are interested in using computer embroidery services. Consumers will be very interested if the catalog can present a form of visualization in the form of a 3-dimensional model that can be seen from various sides. This research implements 3D animation for marketing computer embroidery services using Blender software, the results of which will be used as promotional media. This research uses Blender software and aims to produce 3D animated advertising videos in order to market and promote computer embroidery services as well as as a medium of information and promotion to the public or consumers of computer embroidery services. The results of this research are in the form of advertising videos as promotional media for 3D animation-based computer embroidery services.